2019
DOI: 10.1111/jam.14531
|View full text |Cite
|
Sign up to set email alerts
|

The synergy of resveratrol and alcohol against Helicobacter pylori and underlying anti‐ Helicobacter pylori mechanism of resveratrol

Abstract: Aims To determine individual antibacterial and synergistic antibacterial effects of resveratrol and alcohol against Helicobacter pylori 26695 in vitro, and to elucidate the underlying mechanism of action of resveratrol against H. pylori. Methods and Results The minimum inhibitory concentrations (MICs) and time‐killing curve of resveratrol and alcohol were determined. Transcriptome analysis by RNA sequencing was used to elucidate the underlying mechanism of action of resveratrol against H. pylori. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…According to the literature, resveratrol was able to downregulate the expression of the omp 18 gene (outer membrane protein gene), but the expressions of the ureA (urease) and fla A (flagellin) genes were upregulated ( 58 ). Celecoxib inhibited H. pylori motility by decreasing mRNA expression of the fla A gene, but the ure A gene was upregulated ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, resveratrol was able to downregulate the expression of the omp 18 gene (outer membrane protein gene), but the expressions of the ureA (urease) and fla A (flagellin) genes were upregulated ( 58 ). Celecoxib inhibited H. pylori motility by decreasing mRNA expression of the fla A gene, but the ure A gene was upregulated ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Usually, bacteria downregulate growth and proliferation genes to survive in an unfavorable environment, and the transcription of genes related to survival and virulence is upregulated. Studies have shown that the synergy of resveratrol and ethanol can upregulate the gene transcription of cagA, urease, and other virulence factors of H. pylori 26695 in vitro, and upregulation of genes involved in antioxidation and maintenance of iron homeostasis will facilitate the survival of resveratrol under H. pylori oxidative stress [56,57]. Since the gene expression process of pyloric biofilms is not fully explained at present, only two main virulence factors were selected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, resveratrol, a potent anti-inflammatory and antioxidant polyphenol mostly found in berries, nuts, and grape skin, decreases the levels of IL-8 and inducible nitric oxide synthase and inhibits NF-κB activation in H. pylori-induced gastritis (Zhang et al, 2015). Resveratrol also exerts inhibitory effects on translation, outer membrane protein transport, ATP synthase, and other possible oxidative damage against H. pylori (Xia et al, 2020). Therefore, resveratrol has potential as a treatment option for H. pylori-induced gastritis.…”
Section: Therapeutic Approachesmentioning
confidence: 99%